The presbytery near collegiate church in Klimontów as an example of adaptation of relic with preservation of country noble residence type. - Klimek, Beata (Budownictwo i Architektura / Civil and Architectural Engineering, 2009)
Given in XVI century farm treaties dealt with country building in the context of technical questions (the choice of place under building, building materials, foundations) as well as the principle of planning out the noble seat. The presbytery introduced in the article links to historical country noble residence. Executed redecorating works adapted the presbytery to modern needs. The proposed solution of rooms arrangement is the reconstruction of its state in the end of XVII century.